A phylogenetic re‐appraisal of the family Liagoraceae sensu lato (Nemaliales, Rhodophyta) based on sequence analyses of two plastid genes and postfertilization development. Issue 3 (27th April 2015) - Lin, Showe‐Mei; Rodríguez‐Prieto, Conxi; Huisman, John M.; Guiry, Michael D.; Payri, Claude; Nelson, Wendy A.; Liu, Shao‐Lun; Gabrielson, P.
<x xml:space="preserve">Abstract</x> The marine red algal family Liagoraceae sensu lato is shown to be polyphyletic based on analyses of a combined rbcL and psaA data set and the pattern of carposporophyte development. Fifteen of eighteen genera analyzed formed a monophyletic lineage that included the genus Liagora. Nemalion did not cluster with Liagoraceae sensu stricto, and Nemaliaceae is reinstated, characterized morphologically by the formation of the primary gonimolobes by longitudinal divisions of the gonimoblast initial. Yamadaella and Liagoropsis, previously placed in the Dermonemataceae, are shown to be independent lineages and are recognized as two new families Yamadaellaceae and Liagoropsidaceae. Yamadaellaceae is characterized by two gonimoblast initials cut off bilaterally from the fertilized carpogonium and diffusely spreading gonimoblast filaments. Liagoropsidaceae is characterized by at least three gonimoblast initials cut off by longitudinal septa from the fertilized carpogonium. In contrast, Liagoraceae sensu stricto is characterized by a single gonimoblast initial cut off transversely or diagonally from the fertilized carpogonium. Reproductive features, such as diffuse gonimoblasts and unfused carpogonial branches following postfertilization, appear to have evolved on more than one occasion in the Nemaliales and are therefore not taxonomically diagnostic at the family level, although they may be useful in recognizing genera.